God and Elizabeth Bishop - Walker, C. author. aut Link
XI, 157 p.
Keywords: In God and Elizabeth Bishop Cheryl Walker takes the bold step of looking at the work of Elizabeth Bishop as though it might have something fresh to say about religion and poetry. Going wholly against the tide of recent academic practice, especially as applied to Bishop, she delights in presenting herself as an engaged Christian who nevertheless believes that a skeptical modern poet might feed our spiritual hungers. This is a book that reminds us of the rich tradition of religious poetry written in English, at the same time taking delicious detours into realms of humour, social responsibility, and mysticism.